Functional Indicators in Skaters from the Norte de Santander Selection Using a Cycle Ergometer Test (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2021)
Speed skating, like other sports, requires athlete evaluation to maintain effective sports monitoring; however, in our region, such assessments are scarce. Consequently, the objective was to monitor the physiological variables of Maximum Heart Rate (HRmax), VO2max, and Anaerobic Threshold (AT) in skaters from the Norte de Santander Department Selection using a cycle ergometer test.A descriptive-exploratory, correlational study with a quantitative approach was conducted, using a purposive non-probabilistic sample composed of four men (age 16.50±1.73 years; height 1.62±0.08 m; body weight 59.88±9.55 kg) and four women (age 19.50±6.45 years; height 1.64±0.11 m; body weight 59.58±14.96 kg) with extensive skating experience. The test employed a Monark cycle ergometer and a POLAR heart rate monitor to obtain values for Maximum Power (MP), Workload (WL), VO2max, and HRmax.Data analysis was performed using PSPP software, calculating means and standard deviations, and a Mann-Whitney U test was applied to compare means between genders. The results from the Student’s t-test showed significant differences in maximum power and workload between genders (p